Geoscience of Climate and Energy 12. Water Quality Issues in the Oil Sands Region of the Lower Athabasca River, Alberta - Schindler, David (Geoscience Canada, 2013)
SUMMARY I summarize the controversies about industrial pollutants in freshwaters near the oil sands industrial area of Alberta, the inadequacies in environmental monitoring that have led to widespread misconceptions, and recent attempts to correct the problems. Adequate data are available to show that mercury, other trace metals, and polycyclic aromatic compounds are being added by industry to the Athabasca river system and its watershed, although the relative contributions of industrial development and natural sources remain in question. Recent improvements in water monitoring by Environment Canada show promise of resolving the controversies, although independent governance for Canada’s and Alberta’s water monitoring programs in the lower Athabasca River will be necessary to rebuild public confidence in the data and their interpretation by government and industry. I document one success story in the Athabasca River: the elimination of dioxins from pulp mills in the mid-1990s has caused a consumption advisory for fish in the river to be repealed.